Exploitation of white-lipped peccaries Tayassu pecari (Artiodactyla: Tayassuidae) on the Osa Peninsula, Costa Rica - Altrichter, Mariana (2002)
We studied movements of white-lipped peccaries (Tayassu pecari, Artiodactyla, Tayassuidae) throughout the Osa Peninsula and their use by local people during 1997-2000, using interview techniques. We draw five main conclusions: 1) White-lipped peccaries living on the Osa Peninsula range within Corcovado National Park for most of the year. 2) Peccaries travel beyond the Park boundaries to the north and south-east of the Peninsula at the end of the wet season when a fruit shortage occurs in Corcovado. 3) The local people hunt peccaries as the herds move through the Peninsula. 4) Current small herd sizes observed by locals in the Peninsula and by researchers in the Park may indicate a decline of the peccary population. 5) Peccaries constitute neither an important source of food nor a source of cash income for local people. We suggest that sustainable use of peccaries in this region is neither realistic nor necessary. Instead of trying to legalize and regulate hunting, effective systems to control illegal hunting should be implemented, especially outside the Park boundary from October to January when the animals are on the move. © 2002 FFI